Correlation between Chest CT Severity Scores and the Clinical Parameters of Adult Patients with COVID-19 Pneumonia - Ghufran Aref Saeed; Waqar Gaba; Asad Shah; Abeer Ahmed Al Helali; Emadullah Raidullah; Ameirah Bader Al Ali; Mohammed Elghazali; Deena Yousef Ahmed; Shaikha Ghanam Al Kaabi; Safaa Almazrouei (Radiology Research and Practice)
Purpose. Our aim is to correlate the clinical condition of patients with COVID-19 infection with the 25-point CT severity score by Chang et al. (devised for assessment of ARDS in patients with SARS in 2005). Materials and Methods. Data of consecutive symptomatic patients who were suspected to have COVID-19 infection and presented to our hospital were collected from March to April 2020. All patients underwent two consecutive RT-PCR tests and had a noncontrast HRCT scan done at presentation. From the original cohort of 1062 patients, 160 patients were excluded leaving a total number of 902 patients. Results. The mean age was 44.2 ± 11.9 years (85.3% males, 14.7% females). CT severity score was found to be positively correlated with lymphopenia, increased serum CRP, d-dimer, and ferritin levels (p<0.0001). The oxygen requirements and length of hospital stay were increasing with the increase in scan severity. Conclusion. The 25-point CT severity score correlates well with the COVID-19 clinical severity. Our data suggest that chest CT scoring system can aid in predicting COVID-19 disease outcome and significantly correlates with lab tests and oxygen requirements.